Society's Entrepreneurship During The Pandemic Through The Water Hyacinth Handicraft in The Village of Walahar Klari Distric of West Java - Eliza Rahmah Prahestiwi; Ade Sadikin; Lip Saripah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the problem of the impact of the Covid 19 pandemic which resulted in many people being unemployed and the large number of water hyacinth plants were only considered garbage in Walahar. This condition is seen as an opportunity and a challenge in exploiting the potential of the region. Efforts to overcome this are by opening job vacancies, making entrepreneurial training from raw materials for water hyacinth waste. The objectives of this study are to: a). Obtaining information about increasing community entrepreneurship during the Covid 19 pandemic through water hyacinth crafts. b). To find out what the supporting and inhibiting factors are. c). To find out the results of increasing community entrepreneurship during the Covid 19 pandemic through water hyacinth handicrafts (case study in Desa Walahar Kec. Klari Kab. Karawang Prov. Jawa Barat). To answer the formulation of research problems that have been formulated, the author uses a qualitative approach with the case study method. To explain the phenomena that appear in the field. The research sources are: a). Sources of information, namely the chairman and owner of water hyacinth handicrafts UKM Kab. Karawang "UKM Putri Eceng" namely Mrs. Sambinah; and the Head of the Dinas Koperasi & UMKM Kab. Karawang; who can provide data. b). Informant sources, namely three freelance or community employees who work in the UKM Putri Eceng Kab. Karawang. The results of this study indicate that using a SWOT analysis (Strength, Weaknesses, Opportunities, and Threats as follows: (1) Strength: getting support from husbands, families, communities, the Government of Karawang Regency, Central Government, Consumers, getting capital and support from private companies, can read business opportunities in the market. (2) Weaknesses: Raw materials that will decrease over time, weather for drying water hyacinths, and initial capital to establish entrepreneurship. (3). Opportunities: improving the economy, selling handicrafts, utilizing abundant water hyacinth waste, generating income (money), introducing local tourism and culture, increasing creativity and innovation in entrepreneurship, creating job vacancies for the local community. (4) Threats: competitors of fellow entrepreneurs who process water hyacinth in the marketing world.